A New Method for the Detection of Lesch-Nyhan Heterozygotes by Peripheral Blood T Cell Culture Using T Cell Growth Factor - Kamatani, Naoyuki; Yamanaka, Hisashi; Nishioka, Kusuki; Nakamura, Tsuneyoshi; Nakano, Kei-ichiro; Tanimoto, Kiyoaki; Mizuno, Tei-ichi; Nishida, Yutaro (Blood, 1984)
Thieguanine-resistant T lymphoblast populations were selectively amplified using T cell growth factor in the cultures of peripheral blood T cells from four Lesch-Nyhan heterozygotes. Although Lesch-Nyhan T lymphoblasts were all thioguanine-resistant, none of the cultures from 13 control subjects yielded the growth of such defective cell populations. These data provide direct evidence for the existence of a small percentage (5%-40%) of hypoxanthine-guanine phosphoribosyltransferase (HGPRT) deficient T cells in the heterozygotes, but not in normal individuals. Conversely, culture of the T lymphoblasts with azaserine plus hypoxanthine permitted the growth of the other part of the cell population that was enzyme positive. The low percentages of HGPRT-negative cells among T cells in heterozygotes suggest that the presence of this enzyme is beneficial for differentiation of lymphocytes of T cell linkage. Considering the ease and the reliability, culture of the peripheral T cells with thioguanine and T cell growth factor is very likely of practical use for detecting Lesch-Nyhan syndrome carriers among predisposed females.